Improving Student Learning Outcomes on the Concept of Momentum and Impulse Using the Discovery Learning Model through a Differentiated Approach at SMA Negeri 1 Gorontalo Utara - Basri A Haseng; Abdul Haris Odja; Dewa Gede Eka Setiawan (Physics Education Research Journal, 2025)
This study aimed to improve students’ learning outcomes on the topic of momentum and impulse through the implementation of the Discovery Learning model integrated with a differentiated instructional approach. The study employed a classroom action research design involving 34 students of Class X MIA 4 and was conducted in two action cycles. Each cycle consisted of planning, implementation, observation, and reflection stages, with students’ learning outcomes assessed through a cognitive achievement test administered at the end of each cycle. The results showed that the predetermined success criterion was not achieved in Cycle I, where only 14 of the 34 students attained the minimum mastery criterion, resulting in a classical mastery level of 41%. After revising the instructional strategy, students’ performance improved substantially in Cycle II, with 30 students achieving mastery and a classical mastery level of 88%, exceeding the predetermined success criterion of 80%. These findings indicate that integrating the Discovery Learning model with differentiated instruction effectively improves students’ learning outcomes on the topic of momentum and impulse.